(untitled) (Medical Forum Monthly, 2024)
Objective: This retrospective study examines the role of pre-operative shortening evaluation in surgical planning and open reduction correction in pediatric patients with hip developmental dysplasia. Study Design: A retrospective research Place and Duration of Study: This study was conducted at the Department of Orthopedic, Khyber Teaching Hospital (KTH), Peshawar from January 2021 to January 2022. Methods: A retrospective research examines pre-operative shortening assessments and peri-operative shortening correction in hip developing dysplasia surgery. The study included 95 hip-developmental dysplasia-diagnosed children aged 2–10. Results: The research included 95 individuals diagnosed with hip dysplasia, with a predominant proportion of females (50.53%) and the majority falling between the age range of 5-7 years (42.10%). The pre-operative X-ray measurements revealed a mean Hilgenreiner's angle of 28.5 degrees and an acetabular index angle of 30.8 degrees. The majority of patients (68.42%) were classed as mild hip dysplasia. A strong negative association was seen between pre-operative shortening and peri-operative correction, showing that a larger pre-operative shortening was associated with a greater surgical correction. Conclusion: This study sheds light on pediatric hip dysplasia surgery. Open reduction with capsulorrhaphy and osteotomy was performed in most moderate hip dysplasia patients.